Identifying the Naphthalene-Based Compound 3,5-Dihydroxy 2-Napthoic Acid as a Novel Lead Compound for Designing Lactate Dehydrogenase-Specific Antibabesial Drug - Yu, Long; Zhan, Xueyan; Liu, Qin; Sun, Yali; Li, Muxiao; Zhao, Yangnan; An, Xiaomeng; Tian, Yu; He, Lan; Zhao, Junlong (Frontiers in Pharmacology, 2020)
Human babesiosis is caused by apicomplexan Babesia parasites, including Babesia microti, Babesia crassa, Babesia sp. MOI, Babesia divergens, Babesia duncani, and Babesia venatorum. Among them, B. microti is the most common cause of human and rodent babesiosis. Currently, no vaccine is available, and drugs for the treatment have high failure rates and side effects. Due to lack of a traditional tricarboxylic acid cycle (TCA cycle) and its dominant dependence on anaerobic metabolism to produce ATP, B. microti lactate dehydrogenase (BmLDH) was assumed to play a critical role in B. microti ATP supply. Our previous study demonstrated that BmLDH is a potential drug target and Arg99 is a crucial site. Herein, a molecular docking was performed based on the crystal structure of BmLDH from a series of gossypol derivatives or structural analogs to find the potent inhibitors interacting with the residue Arg99, and three naphthalene-based compounds 2,6-naphthalenedicarboxylic acid (NDCA), 1,6-dibromo-2-hydroxynapthalene 3-carboxylic acid (DBHCA), and 3,5-dihydroxy 2-napthoic acid (DHNA) were selected for further tests. Enzyme activity inhibitory experiments show that DBHCA and DHNA inhibit recombinant BmLDH (rBmLDH) catalysis with 109-fold and 5,000-fold selectivity over human LDH, respectively. Surface plasmon resonance (SPR) assays demonstrate that DHNA has a lower KD value to BmLDH (3.766 x 10−5 M), in contrast to a higher value for DBHCA (3.988 x 10−8 M). A comparison of the kinetic parameters [association constant (ka) and dissociation constant (kd) values] reveals that DBHCA can bind the target faster than DHNA, while the complex of DHNA with the target dissociates slower than that of DBHCA. Both DBHCA and DHNA can inhibit the growth of B. microti in vitro with half-maximal inhibitory concentration (IC50) values of 84.83 and 85.65 μM, respectively. Cytotoxicity tests in vitro further indicate that DBHCA and DHNA have selectivity indexes (SI) of 2.6 and 22.1 between B. microti and Vero cells, respectively. Although the two naphthalene-based compounds only display modest inhibitory activity against both rBmLDH and the growth of B. microti, the compound DHNA features high selectivity and could serve as a novel lead compound for designing LDH-specific antibabesial drug.